Chiefs, land professionals and hybrid planning in Tamale and Techiman, Ghana: Implications for sustainable urban development. Issue 3 (2nd September 2021) - Akaateba, Millicent Awialie; Ahmed, Abubakari; Inkoom, Daniel Kweku Baah
ABSTRACT: A dual land administration system in Ghana necessitates the adoption of hybrid and locally adaptive planning practices. However, whilst the scholarly discourse on hybrid planning is burgeoning, its implications for sustainable urban development are limited. Using qualitative case studies of data collected from interviews and focus group discussions with key stakeholders in Tamale and Techiman, this paper highlights the implications of hybrid planning for sustainable urban development. Although in tune with current proposals for collaborative land use planning, hybrid planning practices in peri-urban areas are dominated by land-owning chiefs who finance land use planning activities, leading to a negotiated planning and land delivery system. This engenders urban sustainability challenges, including tenure insecurities, land speculation and urban sprawl and hinders the realisation of the Sustainable Development Goal 11. Thus, urban planners must re-examine current planning practices and leverage the New Urban Agenda to explore innovative ways of ensuring sustainable urban expansion.